Corrosion and passive behavior of AlxCrFeNi3−x (x = 0.6, 0.8, 1.0) eutectic high entropy alloys in chloride environment. (November 2022) - Zhao, Qiancheng; Pan, Zhimin; Wang, Xuefei; Luo, Hong; Liu, Yang; Li, Xiaogang
Abstract: The corrosion and passive behavior of the as-cast Alx CrFeNi3−x (x = 0.6, 0.8, 1.0 in molar ratio) high entropy alloys in 3.5 wt% NaCl solution at room temperature was investigated by the electrochemical impedance spectroscopy, potentiodynamic polarization measurement, Mott-Schottky measurement, X-ray photoelectron spectroscopy tests, and scanning Kelvin probe force microscopy. The increase of the Al content resulted in the decrease in corrosion resistance, which might be attributed to the reduction of stability and protection of passive films caused by composition difference. Furthermore, the p-type and n-type semiconductor properties of passive films were discussed. Highlights: The corrosion and passive behavior of the as-cast eutectic high entropy alloys in 3.5 wt.% NaCl solution was investigated. The relationship between the composition of alloys and corrosion resistance was presented. Semiconductor properties and chemical compositions of passive films were studied.